Audit Tata Kelola Teknologi Informasi Di RSUD Sekayu Menggunakan Framework Cobit 2019 - Aulia, Aldi Wildan; Ulfa, Maria; Suyanto, S; Ibadi, Taqrim (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Information Technology Governance (IT Governance) is an important concept in managing information technology infrastructure in organizations, including hospitals. This study aims to analyze information technology governance at Sekayu Hospital using the 2019 COBIT framework with a focus on the domains APO12 (Risk Management), APO13 (Security Management), and BAI10 (Configuration Management) at the capability level. This research method involves a case study at Sekayu Hospital, where data is collected through interviews with IT staff, analysis of policy and procedure documents, as well as direct observation of the existing information technology environment. The data is then analyzed with reference to the COBIT 2019 framework, specifically the APO12, APO13, and BAI10 domains by considering the level of capability measured using the COBIT scale, the objects to be evaluated are APO12 – Managed Risk, APO13 – Managed Security and BAI10 – Managed Configuration evaluates by capability level. Objective level capability can be increased by carrying out activities that have not been carried out by Sekayu General Hospital until reaching the full value for each level.